Mediasi Penal Sebagai Alternatif Penyelesaian Perkara Tindak Pidana Lingkungan Hidup - Donu Bani, Ferdinand; Simangunsong, Frans (CV. Era Digital Nusantara, 2023)
This study aims to determine how the role of penal mediation as an alternative in solving environmental crimes outside the court, as well as to determine the construction of penal mediation as an alternative to solving environmental crime cases. Environmental quality degradation is often the result of human actions that are not commendable. Irresponsible and careless actions of humans who pollute and damage the environment are the most fundamental problems regarding difficulties in environmental management. Enforcement of environmental law by means of criminal law has so far been constrained by difficulties in proving that in the end there has been no resolution in several existing environmental cases. Apart from that, proving environmental crimes with criminal penalties requires high human resources and technology. Therefore, the application of penal mediation in resolving environmental crime cases must be carried out because it is beneficial for the environment and in line with the law that lives and develops in a society that already has a mechanism for settling cases through negotiations or deliberations to reach an agreement. This research method uses normative legal research using a statutory approach. The results of the analysis of this study show that penal mediation is an alternative to solving environmental crime cases that are carried out theoretically and more efficiently. Therefore, penal mediation can be used as an alternative solution to environmental crime cases.